Development prospects of hotel аnd restaurant business in Ukraine - Dotsenko, Viktor; Arpul (Oleksiichuk), Oksana; Galynska, Olena; Pushka, Olga (My University, 2017)
The article analyzes the development of hotel and restaurant business in Ukraine. The analysis of the number of accommodation facilities in different areas is presented and the prospects for the development of hotel and restaurant business in Ukraine are determined.
Keywords: hotel and restaurant business; tourism; dynamics; hotel; готельно-ресторанний бізнес; туризм; динаміка; готель; гостинично-ресторанный бизнес; динамика; отель; кафедра готельно-ресторанної справи; кафедра іноземних мов професійного спрямування